2004
DOI: 10.1038/sj.thj.6200364
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function and its clinical significance in the myelodysplastic syndromes

Abstract: The current study was aimed at investigating platelet function in MDS and its clinical significance. There were 23 patients with untreated MDS at presentation, including refractory anemia (RA), RA with ringed sideroblasts, RA and excess blasts and chronic myelomonocytic leukemia RAEBt. The mean platelet count was 167.9 x 109/L. Patients with a platelet count less than 70 x 109/l were excluded. The mean bleeding time (BT) was 2.7 min. Only four MDS patients had BT longer than the normal 1-4 min range. Platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 8 publications
2
13
0
2
Order By: Relevance
“…Recently, a detailed study of the clinical features of 2900 patients with MDS reported that even among patients with platelet counts of Ͼ50,000/l, 19% had signs of bleeding at the time of diagnosis (4). Taken together, these data suggest a platelet count-independent functional platelet defect in MDS, which is supported by sporadic reports indicating insufficient platelet aggregation (3,(5)(6)(7)(8). The existence of such a functional platelet defect may very well contribute to the high rate of hemorrhagic complications observed in patients with MDS.…”
supporting
confidence: 75%
“…Recently, a detailed study of the clinical features of 2900 patients with MDS reported that even among patients with platelet counts of Ͼ50,000/l, 19% had signs of bleeding at the time of diagnosis (4). Taken together, these data suggest a platelet count-independent functional platelet defect in MDS, which is supported by sporadic reports indicating insufficient platelet aggregation (3,(5)(6)(7)(8). The existence of such a functional platelet defect may very well contribute to the high rate of hemorrhagic complications observed in patients with MDS.…”
supporting
confidence: 75%
“…Disturbed maturation of megakaryocytes and ␣-granule defects in platelets are frequent features of MDS (38)(39)(40) and might be reflected by either low CXCL4 expression or a release deficiency in MDS platelets. Our Western blot analyses of platelet lysates showed CXCL4 protein expression in platelet lysates from 9 of 10 non-MDS cytopenia patients but a lack in 7 of 10 MDS platelet lysates.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, Zeidman et al [14] investigated the clinical impact of platelet function in MDS. The study enrolled 23 MDS patients.…”
Section: Discussionmentioning
confidence: 99%
“…No major hemorrhage was observed. However, minor bleeding events occurred in 6 patients; all of them had defective platelet function as tested by aggregation in response to 1 or more agonists [14]. …”
Section: Discussionmentioning
confidence: 99%